Dynamic performance of a multi-mode operation CO2-based system combining cooling and power generation. (15th April 2022) - He, Jintao; Zhang, Yonghao; Tian, Hua; Wang, Xuan; Li, Ligeng; Cai, Jinwen; Shi, Lingfeng; Shu, Gequn
Highlights: Establish dynamic modeling of a multi-mode CO2 -based CCP system. Investigate the dynamic characteristics of the CO2 -based CCP system under different operation modes. The correlation between the power sub-cycle and the refrigeration sub-cycle is weak. Power output will improve when switching integrated refrigeration and power mode to full power mode. Abstract: The CO2 -based combined cooling and power generation system (CCP) is considered as a promising solution for waste heat recovery due to its multiple energy outputs, environmental protection, and compactness. In this work, for waste heat recovery in refrigerated trucks, a dynamic simulation model of a multi-mode CO2 -based CCP system is established in Matlab/Simulink and the experimental data verifies the dynamic simulation model well. The effect of engine heat source, condenser cooling water, and operation mode on the dynamic behavior of the CCP system is analyzed. The results show that the power output will slightly improve when switching from integrated refrigeration and power mode to full power mode. In addition, exhaust gas temperature, flue gas flow, and condenser cooling water temperature are the main disturbance factors affecting the operation of the CCP system. Moreover, in the case of sufficient condenser cooling water, the correlation between the power sub-cycle and the refrigeration sub-cycle of the CO2 -based CCP system is weak, so the two sub-cycles can be controlled independently. The preliminary results presented in this paper will be helpful for the future design and the development of control strategies for the CO2 -based CCP system.